Penerapan UTAUT untuk Mengukur Kepuasan Pelanggan Mobile Banking Perbankan Syariah - Zulkarnain, Muhammad; Junita Safitri; Yulina Astuti (Fakultas Ekonomi dan Bisnis Islam, 2023)
The ever-developing information technology requires that every element of society and companies must innovate and adapt. These developments are also used by banking companies and in this research Islamic banks. The purpose of this study was to determine the level of satisfaction of customers as customers of banks using the Unified Theory of Acceptance and Use of Technology (UTAUT) Model approach. Methods of data analysis using quantitative data with data analysis techniques using Path Analysis. The results of the analysis show an indirect relationship to a significant proposition, among which a significant indirect effect is Interest in using Mobile Banking (BI) affects Bank Customer Satisfaction (CS) through the Use of Mobile Banking (AU) positively and significantly. Facilitating Conditions affect Bank Customer Satisfaction (CS) through the actual use of mobile banking (AU). Social influence (SI) affects the actual use of Mobile Banking (AU) through the interest to use Mobile Banking (BI) in a positive and significant way. In addition, Social Influence (SI) also affects Bank Customer Satisfaction (CS) through the actual Mobile Banking Use (AU) variable positively and significantly